Triple-doped and double-coated lithium iron phosphate material, preparation method thereof and lithium battery

By doping lithium iron phosphate with sodium and vanadium, and using a V-based precursor with a metal-organic framework structure for hydrothermal synthesis, a triple-doped and double-layer-coated lithium iron phosphate material is formed, solving the problem of electrochemical problems of lithium iron phosphate materials. The problem of poor chemical performance is achieved, and a faster Li+ diffusion rate and higher cycle capacity retention rate are achieved.

CN119340367APending Publication Date: 2025-01-21HUNAN YUNENG NEW ENERGY BATTERY MATERIALS CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411477056.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The electrochemical performance of existing lithium iron phosphate (LiFePO4) materials is poor, resulting in the limitation of the application of lithium-ion batteries.

Method used

By doping lithium iron phosphate with sodium (Na) and vanadium (V), and using a V-based precursor with a metal-organic framework structure for hydrothermal synthesis, a triple-doped and double-layer-coated lithium iron phosphate material is formed, namely Li1-xNaxFe1-yVyPO4-C/@ZIF-8. The material is coated through in-situ growth and high-temperature baking of ZIF-8 to form a multi-layered carbon structure, which improves the Li+ diffusion rate and electrochemical performance.

Benefits of technology

It improves the electrochemical performance of lithium-ion battery cathode materials, including faster Li+ diffusion rate and higher cycle capacity retention rate, and solves the problem of poor electrochemical performance of lithium iron phosphate materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119340367A_ABST
    Figure CN119340367A_ABST
Patent Text Reader

Abstract

The invention discloses a triple-doped and double-coated lithium iron phosphate material, a preparation method thereof and a lithium battery, and belongs to the technical field of lithium ion battery materials. The molecular formula is L < i < 1-x > Na < x > Fe < 1-y > V < y > PO < 4-C / (at) ZIF-8; wherein x is more than or equal to 0.01 and less than or equal to 0.03, and y is more than or equal to The tap density is 1.13 to 1.20 g / cm < 3 >, and the compaction density is 2.40 to 2.50 g / cm < 3 >. According to the invention, Li FePO4 is subjected to three-doping with C obtained by calcining a Na, V and VOC2O4 precursor compound, and then in-situ growth calcining coating is carried out with ZIF-8, so that a Zn and graphite sample carbon coating layer is formed, and compared with common LiFeO4, the coated material has a faster L < i + > diffusion rate, and has excellent electrochemical performance when being applied to a lithium battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium ion battery materials, and specifically relates to a triple-doped and double-layer coated lithium iron phosphate material and a preparation method thereof, and a lithium battery. Background Art

[0002] With the change of energy consumption mode and the acceleration of energy revolution, the development of clean and efficient energy storage, conversion and utilization technology has become a current research hotspot. Lithium-ion batteries (LIBs) have been widely used in portable and fixed energy storage systems due to their advantages such as high energy density and long cycle life. As a key component of lithium-ion batteries, positive electrode materials directly affect the performance of lithium-ion batteries. Lithium iron phosphate (LiFePO 4 ) materials have the advantages of low cost, high temperature resistance, high theoretical specific capacity (about 170mA·h / g), no pollution, good stability, and long cycle life, and are widely used in lithium-ion battery positive electrode materials. As a positive electrode material for energy storage batteries, it has been used in new energy vehicles, ships, communication base stations, special medical equipment and other fields. However, due to its own structural limitations, PO 4 Tetrahedron located in FeO 6 Between layers, Li + Diffusion is hindered, and Li + The diffusion channel is single; at the same time, PO 4 Tetrahedral oxygen atoms are separated, FeO 6 The common vertex connection results in low electronic conductivity, which limits the application of lithium iron phosphate electrode materials. Summary of the invention

[0003] One of the purposes of the present invention is to provide a triple-doped and double-layer coated lithium iron phosphate material to solve the existing LiFePO 4 The problem of poor electrochemical performance of materials;

[0004] The second object of the present invention is to provide a method for preparing a triple-doped and double-layer coated lithium iron phosphate material;

[0005] A third object of the present invention is to provide a lithium battery comprising a triple-doped and double-layer coated lithium iron phosphate material.

[0006] The purpose of the present invention can be achieved by the following technical solutions:

[0007] In the first aspect, a triple-doped and double-layer coated lithium iron phosphate material, the molecular formula is Li 1-x Na x Fe 1-y V y PO 4-C / @ZIF-8; 0.01≤x≤0.03, 0.03≤y≤0.08; tap density is 1.13-1.20g / cm 3 , compacted density is 2.40-2.50g / cm 3 .

[0008] In a second aspect, a method for preparing a triple-doped and double-layer coated lithium iron phosphate material comprises the following steps:

[0009] S1. Using water as solvent, add P source to Li source, stir and mix evenly, then add CTAB, stir and mix, then add Na source, Fe source and ascorbic acid, stir and mix evenly; then add V source and stir evenly to obtain a mixed solution, react at 180°C for 8-15h, cool naturally to room temperature (25-30°C), filter, wash, vacuum dry at 70-90°C, and calcine at 600-700°C for 4-6h to obtain Li 1-x Na x Fe 1-y V y PO 4 -C powder;

[0010] S2.Li 1-x Na x Fe 1-y V y PO 4 -C powder was ultrasonically dispersed in methanol, and 2-methylimidazole and Zn(NO 3 ) 2 6H 2 O, stir and mix evenly, react at room temperature for 12-18h, centrifuge, wash, dry, and heat in N 2 , calcined at 600-800℃ for 3-5h to obtain Li 1-x Na x Fe 1-y V y PO 4 -C / @ZIF-8.

[0011] Furthermore, in the mixed solution in S1, the molar ratio of Li:Na:Fe:V:P is 1-x:x:1-y:y:1, 0.01≤x≤0.03, 0.03≤y≤0.08.

[0012] Furthermore, the amount of CTAB in S1 is 0.02-0.04wt% of the total mass of the Li source, Na source, Fe source, V source and P source; the amount of ascorbic acid is 0.9-1.1wt% of the total mass of the Li source, Na source, Fe source, V source and P source.

[0013] Furthermore, the Li source in S1 is LiOH·H 2O、CH 3 COOLi·2H 2 O, LiH 2 PO 4 Any one of the following; P source is H 3 PO 4 NH 4 H 2 PO 3 Any one or combination of the following; Fe source is FeSO 4 7H 2 O、FeC 2 O 4 ·2H 2 O any one; Na source is NaNO 3 .

[0014] Furthermore, the V source in S1 is VOC 2 O 4 Precursor complex, the VOC 2 O 4 The method for preparing the precursor complex comprises the following steps:

[0015] Ammonium metavanadate (NH 4 VO 3 ) and C 2 H 2 O 4 2H 2 O is dissolved in glass fiber drawing wastewater, refluxed and heated to 85-95℃, stirred and reacted for 20-30min, then resorcinol and formaldehyde solution are added, and the reaction is continued for 40-80min, and then filtered, washed and dried to obtain VOC 2 O 4 Precursor complex;

[0016] Furthermore, the NH 4 VO 3 , C 2 H 2 O 4 2H 2 The dosage ratio of O, resorcinol, formaldehyde solution and glass fiber drawing wastewater is 2-4g:3g:0.2g:0.3g:100mL.

[0017] Furthermore, the mass concentration of the formaldehyde solution is 30-40%.

[0018] Furthermore, Li in S2 1-x Na x Fe 1-y V y PO 4 -C powder, 2-methylimidazole and Zn(NO 3 )2 6H 2 The dosage ratio of O is 1-3:1.5:1.

[0019] In a third aspect, a lithium battery, wherein the positive electrode material is the triple-doped and double-layer coated lithium iron phosphate material prepared by the above method.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] 1. The triple-doped and double-layer coated lithium iron phosphate material provided by the present invention has a molecular formula of Li 1-x Na x Fe 1-y V y PO 4 -C / @ZIF-8, 0.01≤x≤0.03, 0.03≤y≤0.08; Na, V and V-based MOF (VOC 2 O 4 Precursor composite) C after calcination on LiFePO 4 After triple doping, ZIF-8 is in-situ grown, calcined and coated and applied in lithium batteries, showing excellent electrochemical properties.

[0022] 2. Glass fiber drawing wastewater is the wastewater discharged during the glass fiber spinning process. Direct discharge will cause harm to the environment and human body. However, there are various solvents and surfactants in the wastewater, and the structure contains hydrophobic and hydrophilic functional groups, as well as lone pair electron nucleation sites. The present invention uses glass fiber drawing wastewater to adsorb metal ions as organic ligands, and hybridizes with ammonium metavanadate to form a V-based precursor with a metal organic framework structure. The preparation cost is low while solving the problem of wastewater discharge.

[0023] 3. VOC 2 O 4 The precursor complex is used as a V source and Li, Fe, P, and Na sources to hydrothermally synthesize lithium iron phosphate doped with various ions. During the calcination process, the organic ligands in the V-based precursor are in situ carbonized, so that the LiNaFeVP particles form a multilayer carbon structure. In addition, VOC 2 O 4 The precursor composite is used as a V source to partially dope the Fe site, which can shorten the LiFePO 4 The band gap of the battery can be further improved by replacing some Li sites with alkali metal Na, which can broaden the one-dimensional diffusion channel of Li. +It has a faster deintercalation speed and improves capacity retention. The lithium iron phosphate material synthesized by hydrothermal method is then in-situ synthesized by high temperature calcination and carbonization coating of Zn-based metal organic framework ZIF-8. Its regular polyhedral morphology and ordered pore structure provide a carbon matrix for lithium iron phosphate, expand the contact area between the electrode material and the electrolyte, and increase the ion diffusion rate, thereby further improving the diffusion kinetics of the electrode material.

[0024] 4. In Li 1-x Na x Fe 1-y V y PO 4 In the -C / @ZIF-8 material, carbon exists in a non-crystalline form, and Na and V occupy the Li and Fe positions respectively, dissolving into the lithium iron phosphate material to form a solid solution. Since the ionic radius of Na is larger than that of Li, and the ionic radius of V is the same as that of Fe, Li + The V source with metal organic framework structure is used, and the multilayer carbon after calcination forms a buffer layer inside the lithium iron phosphate material, reducing unnecessary contact between the positive electrode material and the electrolyte, thereby improving the cycle efficiency. 1-x Na x Fe 1-y V y PO 4 -C surface forms Zn and graphite-like carbon coating, compared with ordinary LiFeO 4 , the coated material has a faster Li + Diffusion rate. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] The present invention will be further described below in conjunction with the accompanying drawings.

[0026] Figure 1 The molecular formula of the present invention is Li 1-x Na x Fe 1-y V y PO 4 -C / @ZIF-8 structural diagram of triple-doped and double-layer coated lithium iron phosphate material. DETAILED DESCRIPTION

[0027] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] VOC2 O 4 The method for preparing the precursor complex comprises the following steps:

[0029] NH 4 VO 3 , C 2 H 2 O 4 2H 2 O, resorcinol, formaldehyde solution and glass fiber drawing wastewater were mixed in a dosage ratio of 2-4g: 3g: 0.2g: 0.3g: 100mL. 4 VO 3 and C 2 H 2 O 4 2H 2 O is dissolved in the wastewater of glass fiber drawing, refluxed and heated to 85-95°C, stirred at 200rpm for 20-30min, and then resorcinol and 30-40% formaldehyde solution are added, and the reaction is continued for 40-80min, and then filtered, washed and dried to obtain VOC 2 O 4 Precursor complex.

[0030] A triple-doped and double-coated lithium iron phosphate material, see Figure 1 The structural diagram shown is Li 1-x Na x Fe 1-y V y PO 4 -C / @ZIF-8, where 0.01≤x≤0.03, 0.03≤y≤0.08;

[0031] The Li 1-x Na x Fe 1-y V y PO 4 -C / @ZIF-8 preparation method, comprising the following steps:

[0032] S1. Li: Na: Fe: V: P weigh Li source, Na source, Fe source, V source and P source according to the molar ratio of 1-x: x: 1-y: y: 1, 0.01≤x≤0.03, 0.03≤y≤0.08;

[0033] Using water as solvent, add P source to Li source, stir and mix evenly at 300 rpm, then add 0.02-0.04%×m (Li source + Na source + Fe source + V source + P source) of CTAB, stir and mix, then add Na source, Fe source and 0.9-1.1%×m (Li source + Na source + Fe source + V source + P source) of ascorbic acid, stir and mix evenly;

[0034] Add VOC 2 O 4 The precursor complex is stirred evenly to obtain a mixed solution, reacted at 180°C for 8-15h, naturally cooled to room temperature, filtered, washed, vacuum dried at 70-90°C, and calcined at 600-700°C for 4-6h to obtain Li 1-x Na x Fe 1-y V y PO 4 -C powder;

[0035] S2.Li 1-x Na x Fe 1-y V y PO 4 -C powder, 2-methylimidazole and Zn(NO 3 ) 2 6H 2 O is weighed according to the mass ratio of 1-3:1.5:1;

[0036] Li 1-x Na x Fe 1-y V y PO 4 -C powder was ultrasonically dispersed in methanol, and 2-methylimidazole and Zn(NO 3 ) 2 6H 2 O, stir and mix evenly, react at room temperature for 12-18h, centrifuge, wash, dry, and heat in N 2 , calcined at 600-800℃ for 3-5h to obtain Li 1-x Na x Fe 1-y V y PO 4 -C / @ZIF-8.

[0037] A lithium battery, wherein the positive electrode material is the triple-doped and double-layer coated lithium iron phosphate material Li prepared by the above method 1- x Na x Fe 1-y V y PO 4 -C / @ZIF-8.

[0038] Example 1

[0039] VOC 2 O 4 The method for preparing the precursor complex comprises the following steps:

[0040] NH 4 VO 3 , C 2 H 2 O 4 2H 2 O, resorcinol, formaldehyde solution and glass fiber drawing wastewater were mixed in the ratio of 3g:3g:0.2g:0.3g:100mL. 4 VO 3 and C 2 H 2 O 4 2H 2 O was dissolved in the wastewater of glass fiber drawing, refluxed and heated to 90°C, stirred at 200rpm for 25min, and then resorcinol and 35% formaldehyde solution were added. After continuing the reaction for 60min, VOC was obtained by filtration, washing and drying. 2 O 4 Precursor complex.

[0041] Example 2

[0042] A triple-doped and double-layer coated lithium iron phosphate material with the molecular formula Li 0.98 Na 0.02 Fe 0.95 V 0.05 PO 4 -C / @ZIF-8, where x=0.02, y=0.05;

[0043] Li 0.98 Na 0.02 Fe 0.95 V 0.05 PO 4 -C / @ZIF-8 preparation method, comprising the following steps:

[0044] S1. Li: Na: Fe: V: P weigh CH according to the molar ratio of 0.98: 0.02: 0.95: 0.05: 1 3 COOLi·2H 2 O.NaNO 3 、FeC 2 O 4 ·2H 2 O. VOC prepared in Example 1 2 O 4 Precursor complex and H 3 PO 4 ;

[0045] Using water as solvent, H 3 PO 4 Join CH 3In the COOLi solution, stir at 300 rpm to mix evenly, then add 0.03%×m (Li source + Na source + Fe source + V source + P source) of CTAB, stir and mix, then add Na source, Fe source and 1%×m (Li source + Na source + Fe source + V source + P source) of ascorbic acid, stir and mix evenly;

[0046] Add VOC 2 O 4 The precursor complex was stirred evenly to obtain a mixed solution, reacted at 180°C for 8-15h, naturally cooled to room temperature, filtered, washed, vacuum dried at 80°C, and calcined at 650°C for 5h to obtain Li 0.98 Na 0.02 Fe 0.95 V 0.05 PO 4 -C powder;

[0047] S2.Li 0.98 Na 0.02 Fe 0.95 V 0.05 PO 4 -C powder, 2-methylimidazole and Zn(NO 3 ) 2 6H 2 O is weighed according to the mass ratio of 2:1.5:1;

[0048] Li 0.98 Na 0.02 Fe 0.95 V 0.05 PO 4 -C powder was ultrasonically dispersed in methanol, and 2-methylimidazole and Zn(NO 3 ) 2 6H 2 O, stirred and mixed evenly, reacted at room temperature for 16 h, centrifuged, washed, dried, and heated in N 2 , calcined at 700℃ for 4h to obtain Li 0.98 Na 0.02 Fe 0.95 V 0.05 PO 4 -C / @ZIF-8.

[0049] Example 3

[0050] A triple-doped and double-layer coated lithium iron phosphate material with the molecular formula Li 0.99 Na 0.01 Fe 0.97 V 0.03 PO 4 -C / @ZIF-8, where x = 0.01, y = 0.03;

[0051] The Li 0.99 Na 0.01 Fe 0.97 V 0.03 PO 4 The preparation method of -C / @ZIF-8 is different from that of Example 2 in that, in S1, Li:Na:Fe:V:P are weighed according to the molar ratio of 0.99:0.01:0.97:0.03:1. 3 COOLi·2H 2 O.NaNO 3 、FeC 2 O 4 ·2H 2 O. VOC prepared in Example 1 2 O 4 Precursor complex and H 3 PO 4 ; The rest of the steps and parameters remain the same.

[0052] Example 4

[0053] A triple-doped and double-layer coated lithium iron phosphate material with the molecular formula Li 0.97 Na 0.03 Fe 0.92 V 0.08 PO 4 -C / @ZIF-8, where x=0.03, y=0.08;

[0054] The Li 0.97 Na 0.03 Fe 0.92 V 0.08 PO 4 The preparation method of -C / @ZIF-8 is different from that of Example 2 in that, in S1, Li:Na:Fe:V:P are weighed according to the molar ratio of 0.97:0.03:0.92:0.08:1. 3 COOLi·2H 2 O.NaNO 3 、FeC 2 O 4 ·2H 2 O. VOC prepared in Example 1 2 O 4 Precursor complex and H 3 PO 4 ; The rest of the steps and parameters remain the same.

[0055] Comparative Example 1

[0056] A lithium iron phosphate material with the molecular formula Li 0.98 Na 0.02 Fe 0.95V 0.05 PO 4 -C, the preparation method thereof is different from that of Example 2 in that the related operations of S2 are not performed, and the other steps and parameters remain the same.

[0057] Comparative Example 2

[0058] A lithium iron phosphate material with the molecular formula Li 0.98 Na 0.02 Fe 0.95 V 0.05 PO 4 / @ZIF-8, the preparation method thereof is different from that of Example 2 in that, in S1, the V source is NH 4 VO 3 , the rest of the steps and parameters remain the same.

[0059] Comparative Example 3

[0060] A lithium iron phosphate material with the molecular formula Li 0.98 Na 0.02 Fe 0.95 V 0.05 PO 4 -C / @C, the difference between its preparation method and embodiment 2 is:

[0061] S2.Li 0.98 Na 0.02 Fe 0.95 V 0.05 PO 4 -C powder was immersed in glucose solution, the amount of glucose was Li 0.98 Na 0.02 Fe 0.95 V 0.05 PO 4 The mixture was stirred for 3 h, centrifuged, washed, and dried. 2 , calcined at 600℃ for 4h to obtain Li 0.98 Na 0.02 Fe 0.95 V 0.05 PO 4 -C / @C;

[0062] The remaining steps and parameters remain the same.

[0063] Comparative Example 4

[0064] A lithium iron phosphate material with the molecular formula LiFePO 4 / @ZIF-8, the preparation method thereof comprises the following steps:

[0065] Commercial LiFePO 4 , 2-methylimidazole and Zn(NO3 ) 2 6H 2 O is weighed according to the mass ratio of 2:1.5:1;

[0066] Commercialization of LiFePO 4 Ultrasonic dispersion in methanol, adding 2-methylimidazole and Zn(NO 3 ) 2 6H 2 O, stirred and mixed evenly, reacted at room temperature for 16 h, centrifuged, washed, dried, and heated in N 2 , calcined at 700℃ for 4h to obtain LiFePO 4 / @ZIF-8.

[0067] Comparative Example 5

[0068] A lithium iron phosphate material with the molecular formula LiFePO 4 / @C, the preparation method thereof comprises the following steps:

[0069] Commercialization of LiFePO 4 Immersed in glucose solution, the amount of glucose used is commercial LiFePO 4 The mixture was stirred for 3 h, centrifuged, washed, dried, and heated to N 2 , calcined at 600℃ for 4h to obtain LiFePO 4 / @C;

[0070] The physical and chemical properties of the lithium iron phosphate materials prepared in Example 2 to Example 4 and Comparative Example 1 to Comparative Example 5 are shown in Table 1:

[0071] Table 1

[0072]

[0073]

[0074] The lithium iron phosphate materials prepared in Examples 2 to 4 and Comparative Examples 1 to 5 were assembled into lithium batteries using the following method:

[0075] The specific assembly method is as follows:

[0076] Conductive carbon black was added to the polyvinylidene fluoride (PVDF) aqueous solution, and then the lithium iron phosphate materials prepared in Examples 2-4 and Comparative Examples 1-5 were added as the positive electrode materials, and NMP was used as the solvent to stir evenly. The slurry was evenly coated on the aluminum foil on the coating machine to make the electrode. The coated electrode was placed in a vacuum drying oven at a temperature of 120°C and vacuum dried for 6 hours. The electrode was taken out and rolled on a roller press for use. The battery was assembled in a glove box under an argon atmosphere, and the electrolyte was 1M LiPF6 + Ethyl carbonate (EC): dimethyl carbonate (DEC): diethyl carbonate (DMC) = 1:1:1 (v / v), the metal lithium sheet is the counter electrode.

[0077] The capacity test was carried out on an American Arbin BT2000 battery tester with a charge and discharge voltage range of 2.5-4.2 V. The test results of the first discharge specific capacity at 0.1C and 1C rates and the capacity retention rate after 150 cycles at 1C rate are shown in Table 2.

[0078] Table 2

[0079]

[0080]

[0081] It can be seen from the test results in Table 1 and Table 2 that the present invention reduces the LiFePO by doping Na and V into lithium iron phosphate, using Na to replace part of the Li position and V to replace part of the Fe position. 4 The band gap of the battery is further improved; the V source adopts a V-based precursor with a metal organic framework structure. After carbonization, the lithium iron phosphate is doped with C and a multi-layer buffer carbon structure is formed in the lithium iron phosphate to achieve a high cycle capacity retention rate.

[0082] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0083] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A triple-doped and double-layer coated lithium iron phosphate material, characterized in that: The molecular formula is Li 1-x Na x Fe 1-y V y PO4-C / @ZIF-8; 0.01≤x≤0.03, 0.03≤y≤0.08; tap density is 1.13-1.20g / cm 3 , compacted density is 2.40-2.50g / cm 3 .

2. A method for preparing the triple-doped and double-layer coated lithium iron phosphate material as claimed in claim 1, characterized in that: The following steps are involved: S1. Using water as solvent, add P source to Li source, stir and mix evenly, then add CTAB, stir and mix, then add Na source, Fe source and ascorbic acid, stir and mix evenly; then add V source and stir evenly to obtain a mixed solution, react at 180°C for 8-15h, cool naturally to room temperature, filter, wash, vacuum dry at 70-90°C, and calcine at 600-700°C for 4-6h to obtain Li 1- x Na x Fe 1-y V y PO4-C powder; S2.Li 1-x Na x Fe 1-y V y PO4-C powder was ultrasonically dispersed in methanol, 2-methylimidazole and Zn(NO3)2·6H2O were added, stirred and mixed evenly, reacted at room temperature for 12-18h, centrifuged, washed and dried, and calcined under N2 at 600-800℃ for 3-5h to obtain Li 1-x Na x Fe 1-y V y PO4-C / @ZIF-8.

3. The method for preparing a triple-doped and double-layer coated lithium iron phosphate material according to claim 2, characterized in that: The V source is a VOC2O4 precursor compound, and the preparation method of the VOC2O4 precursor compound comprises the following steps: Dissolve NH4VO3 and C2H2O42H2O in glass fiber drawing wastewater, reflux and heat to 85-95°C, stir and react for 20-30 minutes, then add resorcinol and formaldehyde solution, continue to react for 40-80 minutes, filter, wash and dry to obtain a VOC2O4 precursor complex.

4. The method for preparing a triple-doped and double-layer coated lithium iron phosphate material according to claim 3, characterized in that: The dosage ratio of NH4VO3, C2H2O42H2O, resorcinol, formaldehyde solution and glass fiber drawing wastewater is 2-4g:3g:0.2g:0.3g:100mL.

5. The method for preparing a triple-doped and double-layer coated lithium iron phosphate material according to claim 3, characterized in that: The mass concentration of the formaldehyde solution is 30-40%.

6. The method for preparing a triple-doped and double-layer coated lithium iron phosphate material according to claim 2, characterized in that: The amount of CTAB in S1 is 0.02-0.04wt% of the total mass of the Li source, Na source, Fe source, V source and P source; the amount of ascorbic acid is 0.9-1.1wt% of the total mass of the Li source, Na source, Fe source, V source and P source.

7. The method for preparing a triple-doped and double-layer coated lithium iron phosphate material according to claim 2, characterized in that: S2 1-x Na x Fe 1-y V y The dosage ratio of PO4-C powder, 2-methylimidazole and Zn(NO3)2·6H2O is 1-3:1.5:

1.

8. A lithium battery, characterized in that: The positive electrode material is the triple-doped and double-layer coated lithium iron phosphate material as described in claim 1, Or, a triple-doped and double-layer coated lithium iron phosphate material prepared by the preparation method described in any one of claims 2-7.

Citation Information

Cited By

  • Cladding and doping co-modified lithium iron phosphate positive electrode material, preparation method thereof and battery

    CN122417763A

  • A coated and doped co-modified lithium iron phosphate cathode material, a preparation method thereof and a battery

    CN122417763B